Is disruptive mood dysregulation disorder a precursor for borderline personality disorder? - Martins, Hugo André de Lima (Avanços em Medicina, 2025)
Disruptive mood dysregulation disorder in children and adolescents is characterized by chronic irritability, in which outbursts of anger are manifested either verbally or through aggressive behavior. Before the last update of the Diagnostic and Statistical Manual of Mental Disorder (DSM-5), many severely irritable children were diagnosed with bipolar disorder. A borderline personality disorder is characterized by emotional instability, episodes of anger, impulsivity, and irritability; therefore, it is often misidentified as bipolar disorder. The behavior of disruptive mood dysregulation disorder resembles many characteristics of borderline, which diagnosis usually occurs in young adulthood. Is disruptive mood dysregulation disorder a precursor for borderline disorder?